Microbiology of Anaerobic Sludge Fermentation: I. Enumeration of the Nonmethanogenic Anaerobic Bacteria - Mah, Robert A. (1968)
An anaerobic medium containing sludge supernatant fluid and glucose was used for enumeration of bacteria from the sludge fermentation. Comparison of viable counts from several separate samples consistently showed 10 to 100 times more anaerobic than aerobic bacteria. However, viable counts of the various samples differed by as much as 10 times; this variation probably reflects a change in the natural environment or sampling errors, or a combination of the two. Direct microscopic counts yielded values of about 10(10)/ml. The discrepancy between viable (10(8) to 10(9)/ml) and direct counts may be due to large numbers of dead cells. Random isolates of representative colonies from high dilutions exhibited the ability to ferment sugars and are not likely to be methane bacteria.